Infective Endocarditis: Systemic Inflammatory Response in Preoperative Heart Failure - Koltunova, Hanna B.; Antomonov, Mikhailo Yu.; Rudenko, Olena V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Surgical outcomes depend on several factors, including the choice of surgical procedure, surgical techniques and experience of medical center. Numerous nationwide population-based studies in Europe have shown an increase in the incidence of infective endocarditis (IE) by 4% per year. An important role in predicting the severity of the disease is played by the systemic inflammatory response, which is manifested by increased levels of inflammatory markers such as C-reactive protein and procalcitonin. The use of a complex of several inflammatory markers can potentially improve the analysis of the inflammatory response system and the assessment of treatment dynamics. The aim. To evaluate the dynamics of systemic inflammatory response markers in patients with IE complicated by acute heart failure undergoing cardiopulmonary bypass surgery. Materials and methods. The study included clinical data of 72 patients with IE complicated by preoperative acute heart failure (AHF) who underwent cardiac surgery at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from 01/01/2019 to 12/30/2022. The diagnosis of IE was established in accordance with the Duke criteria. All the patients were classified as NYHA class IV. Results. According to the analysis of systemic inflammatory response markers in patients with IE complicated by AHF at the preoperative stage, the leukocyte count was 10.1 × 109/L (8.1; 14.1), while stab cells accounted for 6.0% (4.0; 8.0). Erythrocyte sedimentation rate was elevated – 27.5 mm per hour (17.0; 50.0). The median body temperature on admission was 37.3 °C (37.1; 38.3). In the early postoperative period, there was a sharp increase in the level of procalcitonin to 2.1 ng/mL, as well as increase in C-reactive protein to 69.33 mg/L. At the same time, an increase in lactate level to 2.24 mmol/L was recorded. On the 7th day of the postoperative period, a decrease in the levels of C-reactive protein and procalcitonin was detected – 34.15 mg/L and 0.2 ng/mL, respectively. In contrast, the lactate level increased to 2.43 mmol/L. Evaluation of biochemical markers of inflammation on postoperative day 14 showed a trend towards normalization: C-reactive protein 28.27 mg/L, procalcitonin 0.1 ng/mL, lactate 2.29 mmol/L. Conclusions. Timely assessment of specific markers of organ dysfunction associated with infectious processes is the basis for diagnosis, risk stratification and ensuring the best treatment outcome. A comprehensive analysis of the levels of biochemical markers of inflammation creates the conditions for choosing a management strategy for patients with IE complicated by AHF.